Pengaruh Kompetensi terhadap Kinerja Karyawan pada PT. Bank BRI Syariah KC. Makassar - Mukhtar, Afiah (Patria Artha Management Journal, 2017)
The Influence Of Competence On Employee Performance At PT. Bank BRI Syariah KC. Makassar. The goal to be achieved in this study is to determine the magnitude of the influence of competence on employee performance. Data Analysis Technique with simple regression analysis with sample number 30 people. The result of the research shows that the competence can increase the employees performance of the variables for X and 0.072X and positive. This means every price increase of one percent then there will be an increase in employee performance of 0.072 times as well as vice versa.